Self-Compassion, Menopause Attitudes, and Social Support as Correlates of Well-Being in Midlife Indonesian Women - Budi Sarasati; Lenny Utama Afriyenti; Dini Iswari (Journal of Islamic Psychology and Behavioral Sciences, 2026)
Psychological well-being in adulthood reflects the interaction of personal psychological resources and social environments, particularly when aging-related bodily changes are shaped by cultural expectations. This study examined the associations of self-compassion, perceived social support, attitudes toward menopause, and optimism with psychological well-being among Indonesian women. Using a cross-sectional survey, data were collected from 147 women aged 18–63 years (M = 45.29, SD = 5.73) through online self-report questionnaires. Measures assessed psychological well-being, self-compassion, perceived social support, attitudes toward menopause, and dispositional optimism. Data were analyzed using reliability testing, Pearson correlations, and HC3 robust multiple regression to address non-normality. Results showed that psychological well-being was positively associated with self-compassion (r = .34, p < .001), perceived social support (r = .48, p < .001), and positive attitudes toward menopause (r = .23, p = .005), whereas optimism was not significantly related (r = .13, p = .117). Robust regression confirmed self-compassion and perceived social support as the strongest predictors, with menopause attitudes contributing modestly and optimism remaining non-significant. These findings highlight the importance of intrapersonal and interpersonal resources for psychological well-being among Indonesian women, particularly during midlife transitions. Although limited by its cross-sectional design and lack of menopausal stage assessment, this study supports culturally informed interventions that strengthen self-compassion and social support.